Pengaruh Kompetensi, Motivasi Dan Desain Pekerjaan Terhadap Kinerja Karyawan Padapt. Sinar Anyar Abadi Muara Enim - Claudia, Henly Cendy; Nilawati, Arniza; Agusria, Lesi (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2026)
This study aims to determine the effect of competence, motivation, and job design on employee performance at PT. Sinar Anyar Abadi Muara Enim. The type of research used is associative research. The population in this study was 62 employees, with a sample of 54 respondents determined using the Slovin formula. The sampling technique used probability sampling. The analysis technique used was multiple linear regression analysis, F test, t test and coefficient of determination with the help of the SPSS program. The results of the simultaneous F test showed that there was a positive and significant influence between competence, motivation, and job design on employee performance at PT. Sinar Anyar Abadi Muara Enim. The results of the partial t test showed that: 1) competence had a positive and significant partial effect on employee performance at PT. Sinar Anyar Abadi Muara Enim, 2) motivation had a positive and significant partial effect on employee performance at PT. Sinar Anyar Abadi Muara Enim, and 3) job design had a positive and significant partial effect on employee performance at PT. Sinar Anyar Abadi Muara Enim. The results of the coefficient of determination (Adjusted R Square) indicate that 68.7% of changes in employee performance can be explained by competency, motivation, and job design, while the remaining 31.3% is influenced by other variables not examined in this study.